Evolution of Landscape-Segmented Nutrient Management (LSNM) Decision Support Tool (DST): A case of Ethiopia - Desta, G. (International Crops Research Institute for the Semi-Arid Tropics, 2023)
Soil fertility and nutrient management is one of the major factors contributing to productivity and optimization of resources especially in water limited areas. Several approaches and tools have been developed over decades such as site specific-nutrient management (SSNM) but with plot-scale applications having limitations for applications to realize the potential benefits due to complex interactions with landscape features. ICRISAT’s landscape-based research approach to develop sustainable systemic solutions is unique for transforming dryland agri-food systems. The Landscape approach is critical for addressing the grand challenges in drylands agriculture; soil fertility and soil health, land degradation, water scarcity, climate change, and biodiversity. The approach is a farmerrelevant, community scale that fits well with local knowledge of soil, hydrology, landscape features, cropping system and agronomic management practices; thus, enables to enhance localized understanding of farming systems and management practices. ICRISAT’s landscape targeted nutrient management approach leads to an optimal nutrient use efficiency that does not lead to environmental (leaching) and economic costs. Since 2014, building on the EthioSIS national initiative, ICRISAT Ethiopia in partnership with NARS (National Agricultural Research Systems) has developed landscape segmented fertilizer decision system support from several projects including Africa RISING, GiZ-ISFM, CGIAR (Consultative Group on International Agricultural Research) WLE (Water, Land and Ecosystems), IFDC-Soil Consortium, CGIAR EiA (Excellence in Agronomy) initiative, and AGRA(Alliance for Green Revolution in Africa). Landscape-Specific Nutrient Management (LSNM) which uses optimized fertilizer application along landscape positions and advanced the approach from a decision guide framework into a digital advisory tool over years. The decision support works with extension agent and lead farmer centered design approach and influences other users through the extension agent network.